Partisipasi Masyarakat Sebagai Agen Perubahan Kurikulum Pendidikan Di Indonesia - Darul lailatul Qomariyah, M. Ag. (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
Global life is something that cannot be avoided, and indeed it is not necessary to avoid it. But the problem is how to empower Muslims to color the global culture. For this reason, the role of Islamic education is very significant in providing provisions for humanity to be able to move swiftly in the area of globalization. In short, the quality of our education is still very concern. Its rank is far below other countries. In addition, the educational problems experienced by Indonesia also cause a decline in the academic moral quality of our education which causes the ultimate purpose of education is never seen and influential in our lives. Although it is recognized that it is still very difficult to see signs that allow our education get a resurgence and have an increasingly large role in the future, we are always required to